Mot händelsernas horisont : Att komponera improviserad musik med ljuddesign som metod - Jonsäll, Hans Lennart (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
This Bachelor Thesis in composition explores an alternative compositional process for creating improvised music through the approach of sound design. The questions addressed in the thesis are concerned with how the soundscape can be controlled by the composer while still maintaining the expressivity of an improvised performance. Thus, the composer’s role as both sound designer, producer and performer is investigated using live electronics and score design. The theoretical framework for the thesis is to be found in the intersection between Anglo-American experimental music, electronic music, sound design and electroacoustic improvisation. Key influences include indeterminacy as expressed in the music of John Cage, Deep Listening practices pioneered by Pauline Oliveros as well as the aesthetical paradigms of electronic and electroacoustic music. The artistic methods revolved around the following steps: studio workshops with musicians (Fredrik Ekenvi and José Louis Relova Gallego) exploring timbres, playing techniques and music technology in real-time followed by associative discussions about the soundscapes created; composing audio and graphical drafts influenced by the workshops; designing diagrams for the electronics and compiling these to a design document; workshopping and performing the final piece (Towards the Event Horizon). Towards the Event Horizon (for bass clarinet, electric guitar and live electronics) is the final result of the work, comprising a score with accompanying design document as well as a recording of the original performance at Studio Acusticum in Piteå 20th of March 2021. The artefacts and associated documentation are presented in their entirety on the dedicated Research Catalogue exposition. Conclusions include how composition and sound design are tied together and cannot be considered as isolated processes, especially in the context of live electronics; the interrelationship between the improviser, the acoustic soundscape and the artistic associations that inform the improvisation; the ...